Maßstäbe demokratischer Legitimation Eine Betrachtung des rechtswissenschaftlichen Diskurses über Demokratiemaßstäbe im deutschen Verfassungsrecht und dem Primärrecht der Europäischen Union - Brandl-Michel, Philipp (Studien zu Staat, Recht und Verwaltung, 2021)
The concept of democratic legitimization is used in various disciplines and also in different legal contexts. However, it is regularly not a matter of one and the same legal standard; rather, German constitutional law and EU primary law appear to contain very different approaches. There are also certain shifts in discourse between jurisprudence and legal scholarship. The thesis differentiates methodologically and disciplinarily in order to put the different positions in relation to each other and to gain a better overview of the discourse.